Epilepsy in resource limited settings : quality for life - Mugumbate, Rugare (Routledge, 2025)
Focused on the understandings and impacts of epilepsy in resource-limited settings, particularly those in the Global South, this important book provides a thorough examination of how the condition can be managed to promote better quality of life.The book is informed by global initiatives, including the Intersectoral Global Action Plan (IGAP) on epilepsy established by the World Health Organisation in 2022. The first two chapters are centred on two broad but competing perspectives on epilepsy, the spiritual and the biological, which are followed by chapters covering the determinants and prevention of epilepsy, and first aid, guidance and counselling. The book moves on to outline the disadvantages, impacts and challenges of epilepsy, as well as initiatives to address the condition at regional and global levels, spotlighting responses in Africa, Asia and the Pacific, the Caribbean, the Middle East and North Africa, and Latin America. The final section of the book focuses on social management, individual resilience and social services, with a concluding chapter outlining a new Integrative Model for Managing Epilepsy (IMME).Written by an author with extensive experience designing and leading epilepsy programmes both internationally and in sub-Saharan Africa, this book will interest Social Work, Public Health, Nursing, Medical, Counselling, Community Health scholars, students and practitioners.
Keywords: Epilepsy.; Quality of life.; elektronické knihy; electronic books